Impact of the System of Air Supply to a Milking Unit on Selected Parameters of Milking Machine Operation (Agricultural Engineering, 2016)
Air is supplied to a milking machine installation most usually in a constant manner by supply of a small amount of air to a milking chamber of a claw or periodically to a connection pipe of a liner, which enables milk outflow to a milking pipe and improves stabilization of vacuum and limits its fluctuations. On the market of milking machines there is a new solution in the form of mouthpiece vented liners - impulseair®, where air is supplied constantly by a calibrated nozzle in the head of a liner. The objective of the paper was to analyse and assess the selected parameters of milking determined in a milking machine with a claw with fixed volume of a milking chamber (250 cm3) with mouthpiece vented liners in comparison to other solutions used for air supply in milking machines. Measurements were carried out in laboratory conditions with milking to the upper milk pipeline, at variable mass intensities of liquid flow (within 0-8 kg·min-1), for three penetrations of artificial teats (46, 48, 62 mm), at three values of the system vacuum (46, 48 and 50 kPa). A significant impact of the manner of air supply to a milking machine and remaining independent variables of an experiment on the selected milking parameters was proved with the use of a statistical analysis. It was found that a milking unit with mouthpiece vented liners, although it reduces average vacuum of suction [pss], at the same time it limits fluctuations of underpressure in the dp cycle.